Small and Smart: Adventures in Epihalohydrin Chemistry - Langer, Peter (Synlett, 2023)
The present personalized account aims to highlight reactions of epichlorohydrin and epibromohydrin with free and masked dianions. These reactions permit convenient syntheses of a variety of products, such as 2-(alkylidene)tetrahydrofurans (which can be further functionalized by hydrogenation or ring-transformation reactions), cyclopropanes, γ-butyrolactams, oxazines, oxazolo[3,4-b]pyridazin-7-ones, or 2-(alkylidene)thiazolidines. In general, the reactions proceed with very good regioselectivity.1 Introduction2 Reactions of Masked Dianions2.1 Synthesis of 2-(Alkylidene)tetrahydrofurans2.2 Functionalization of 2-(Alkylidene)tetrahydrofurans3 Reactions of Free Dianions3.1 Synthesis of 2-(Alkylidene)tetrahydrofurans3.2 Functionalization of 2-(Alkylidene)tetrahydrofurans3.3 Synthesis of γ-Butyrolactams3.4 Synthesis of 5,6-Dihydro-4H-1,2-oxazines3.5 Synthesis of Oxazolo[3,4-b]pyridazin-7-ones3.6 Synthesis of Cyclopropanes3.7 Synthesis of 2-(Alkylidene)thiazolidines4 Conclusions
Keywords: cyclizations; dianions; epoxides; regioselectivity; silyl enol ethers; epihalohydrins